1998
DOI: 10.1038/sj.onc.1202085
|View full text |Cite
|
Sign up to set email alerts
|

Sulindac sulfide inhibits Ras signaling

Abstract: The non-steroidal anti-in¯ammatory drug sulindac is used in cancer prevention and therapy, but the molecular aspects of its anti-tumor eect remain unresolved. In vivo the prodrug sulindac, is converted into the metabolite sulindac sul®de. We found that sulindac sul®de strongly inhibits Ras induced malignant transformation and Ras/ Raf dependent transactivation. Sulindac sul®de decreases the Ras induced activation of its main eector, the cRaf-1 kinase. In vitro sulindac sul®de directly binds to the Ras gene pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
78
0
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(82 citation statements)
references
References 26 publications
(37 reference statements)
2
78
0
2
Order By: Relevance
“…Sulindac sulfide at a concentration of 100 µM caused the most impressive effect. We therefore chose a concentration of 100 µM for all subsequent experiments since this concentration is also consistent with that used in previous studies (Herrmann et al 1998). We found that sulindac sulfide significantly inhibited E2-mediated VDR upregulation in both HT29 and MCF-7 cells, indicating that Ras signaling is involved in E2-mediated VDR transcriptional control.…”
Section: Sulindac Sulfide Inhibits E2-mediated Vdr Expressionmentioning
confidence: 54%
See 1 more Smart Citation
“…Sulindac sulfide at a concentration of 100 µM caused the most impressive effect. We therefore chose a concentration of 100 µM for all subsequent experiments since this concentration is also consistent with that used in previous studies (Herrmann et al 1998). We found that sulindac sulfide significantly inhibited E2-mediated VDR upregulation in both HT29 and MCF-7 cells, indicating that Ras signaling is involved in E2-mediated VDR transcriptional control.…”
Section: Sulindac Sulfide Inhibits E2-mediated Vdr Expressionmentioning
confidence: 54%
“…The ability of sulindac sulfide to inhibit Ras (Herrmann et al 1998) warrants examination whether sulindac sulfide can inhibit other pathways dependent on Ras. To that end, we incubated HT29 and MCF-7 cells with sulindac sulfide (100 µM) in the presence of E2 and tested the effect on VDR expression (Fig.…”
Section: Sulindac Sulfide Inhibits E2-mediated Vdr Expressionmentioning
confidence: 99%
“…Moreover, the caspase inhibitor zVAD-fmk suppressed cell death, Bax was noted to translocate from the cytosol to mitochondria, and cytochrome c release from mitochondria was seen using time-lapse confocal microscopy (Zimmermann et al, 2000). Sulindac sulfide (up to 500 µM tested) can inhibit growth of NIH3T3 and SAOS cells: an inhibtion of ras mediated proliferation and transformation was noted (Herrmann et al, 1998). Hughes et al, (2003) showed that NSAID treatment of colorectal cancer cell lines caused a decrease in intracellular polyamine content and was cytotoxic.…”
Section: Nsaids Signalling Pathways and Apoptosismentioning
confidence: 98%
“…Several lines of evidence suggest that some of the effects of NSAIDs are independent of the inhibition of COX (23). Indeed, it has been shown that NSAIDs modulate COX-independent signaling pathways, such as Ras (24), NFB (25), activator protein-1 (26), ERK (26), p38 kinase (27), and others. Because the role of NSAIDs in the maintenance of homeostasis and apoptosis of articular chondrocytes is not clearly understood, although the action of NSAIDs in inflammation is clear, we investigated the function of various NSAIDs in NO-induced dedifferentiation and apoptosis and characterized the molecular mechanism of NSAIDs action in articular chondrocytes.…”
mentioning
confidence: 99%